2001
DOI: 10.4049/jimmunol.166.7.4689
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Prostaglandin E Receptors EP2 and EP4 and Their Different Regulation by Lipopolysaccharide in C3H/HeN Peritoneal Macrophages

Abstract: The expression and regulation of the PGE receptors, EP2 and EP4, both of which are coupled to the stimulation of adenylate cyclase, were examined in peritoneal resident macrophages from C3H/HeN mice. mRNA expression of EP4 but not EP2 was found in nonstimulated cells, but the latter was induced by medium change alone, and this induction was augmented by LPS. mRNA expression of EP4 was down-regulated by LPS but not by medium change. PGE2 increased the cAMP content of both LPS-treated and nontreated cells. ONO-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 43 publications
(32 reference statements)
6
102
2
Order By: Relevance
“…Alternatively, relative overexpression of EP3 over EP2 may favor an EP3-type response to lower concentrations of PGE 2 . Changes in EP receptor expression profiles can be mediated by several factors known to be increased in ALI including LPS, serum, stress, and IFN-␥, and PGE 2 itself (33,63,64). In fact, fibroblasts isolated from wild-type mice after experimentally induced lung fibrosis exhibit a relative increase in the proportion of EP3 over EP2 receptors, and a switch from a proliferative-suppressive to a proliferative-stimulating response to PGE 2 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, relative overexpression of EP3 over EP2 may favor an EP3-type response to lower concentrations of PGE 2 . Changes in EP receptor expression profiles can be mediated by several factors known to be increased in ALI including LPS, serum, stress, and IFN-␥, and PGE 2 itself (33,63,64). In fact, fibroblasts isolated from wild-type mice after experimentally induced lung fibrosis exhibit a relative increase in the proportion of EP3 over EP2 receptors, and a switch from a proliferative-suppressive to a proliferative-stimulating response to PGE 2 (36).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports that PGE 2 contributes to immune suppression and that PGE 2 secreted from activated macrophages in response to proinflammatory stimuli acts on the macrophages themselves and exhibits an inhibitory function in a negative feedback loop (21). Addition of exogenous PGE 2 has been shown to reduce LPS-induced IL-6 and TNF-␣ production, but not IL-1␤ production, in macrophages (31).…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 has been shown to modulate the production of proinflammatory cytokines (21). Therefore, we analyzed the LPS-induced production of proinflammatory cytokines in mPGES-mutant mice.…”
Section: Normal Production Of Proinflammatory Cytokines In Response Tmentioning
confidence: 99%
“…We consider that this experiment cannot exclude the possibility that EP 2 is weakly expressed in gastric mucosal cells, because it was recently reported (39) that EP 2 is expressed in the stomach of the mouse, using RNase protection assay. Furthermore, it was recently found that the gene encoding EP 2 is inducible in macrophages; EP 2 mRNA was detected only after a change of medium or following the addition of LPS to the medium (41). Therefore, it is also possible that an unknown stimulus under our culture conditions induces EP 2 mRNA expression.…”
Section: Fig 3 Effect Of Pge 2 On Ethanol-induced Release Of Cytochmentioning
confidence: 97%